2013
DOI: 10.1074/jbc.m112.422170
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of IκBα at Serine 32 by T-lymphokine-activated Killer Cell-originated Protein Kinase Is Essential for Chemoresistance against Doxorubicin in Cervical Cancer Cells

Abstract: Background:The regulatory mechanism of TOPK underlying cancer cell survival remains unknown. Results: TOPK directly interacts with and phosphorylates IB␣ at Ser-32. Conclusion: TOPK is a critical mediator of cervical cancer chemoresistance in response to doxorubicin. Significance: This study provides new insight on role of TOPK in cervical cancer cell survival in response to doxorubicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…In addition, Akt also activates IKKα (41)(42)(43). On the other hand, PBK/TOPK directly interacts with and phosphorylates IκBα, leading to NF-κB activation (25). Our results revealed that HI-TOPK-032 suppressed the phosphorylation of IKKα/β and IκBα, suggesting that PBK/TOPK seems to activate NF-κB through direct phosphorylation of IκBα or indirect activation of the PI3K-Akt-IKK signaling pathway by inactivation of PTEN.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, Akt also activates IKKα (41)(42)(43). On the other hand, PBK/TOPK directly interacts with and phosphorylates IκBα, leading to NF-κB activation (25). Our results revealed that HI-TOPK-032 suppressed the phosphorylation of IKKα/β and IκBα, suggesting that PBK/TOPK seems to activate NF-κB through direct phosphorylation of IκBα or indirect activation of the PI3K-Akt-IKK signaling pathway by inactivation of PTEN.…”
Section: Discussionmentioning
confidence: 72%
“…Several reports have demonstrated the potential of TOPK to attenuate apoptosis and enhance antioxidant capacity in cancer cell lines. For example, TOPK has been shown to inhibit As 3+ -induced apoptosis through induction of histone H2AX phosphorylation [16], stable TOPK knockdown increases apoptosis in human colon cancer cells (HCT116) and breast adenocarcinoma cells (MCF-7) via interaction with p53 [17], and doxorubicin-mediated apoptosis in human epithelial carcinoma cell HeLa was found to be noticeably increased after TOPK knockdown by IjBa phosphorylation [18]. In addition, TOPK was shown to prevent apoptosis induced by UVB in RPMI7951 human melanoma cells through phosphorylation of Prx1 and reduced H 2 O 2 accumulation [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fucoidan was reported to directly interact with TOPK kinase and inhibit its kinase activity (23). Furthermore, TOPK directly interacted with and phosphorylated IκBα (24). Therefore, we investigated whether fucoidan influenced the activity of TOPK, an upstream kinase of IκBα.…”
Section: Fucoidan Induces Downregulation Of Cdk4 Cdk6 Bcl-xlmentioning
confidence: 99%